Comparative analysis of hardness and microstructure of dissimilar welded materials at various welding positions in the fabrication industry - Mochammad Karim Al Amin; Ilham Nurcholis; Wiwik Dwi Pratiwi; Dika Anggara; Eriek Wahyu R W (Journal of Welding Technology, 2022)
304 stainless steel is commonly used in industry due to the advantages of great conductivity, while SS 400 carbon steel is largely used in the various engineering field on purpose of industrial and fabrication. One of examples is penstock application in Tegal, Central Java, has been using more than one kind of dissimilar steel, SUS 304 and SS 400, and the various of welding position (1G, 2G, and 3G). Penstock was flowed water from the river for irrigation and raw water so that could be affected to decrease of the thickness of materials. This research was conducted on the dissimilar welding of SUS 304 and SS 400 by SMAW with the welding process of (1G), (2G), and (3). After the welding process, visual examination, hardness test, and microstructure were conducted to examine the quality of welded and hardness of the root and surface of weld. The visual test was shown that no defect, the highest of hardness was at the weld metal with 3G of welding position at 207.17 HVN (specimen 2B) while the lowest of hardness was 195.13 HVN with 2G position (specimen 2A). The microstructure of weld metal was austenite of white and delta-ferrite of black, delta-ferrite was vermicular.